Lacanian Psychoanalytic Explorations of Love within Christianity and Islam - Duane Rousselle (EJP import test, 2020)
Summary: This essay introduces a number of Lacanian psychoanalytic coordinates for understanding love within Christian and Islamic perspectives. It attempts to locate a dialogue between Christian and Islamic discourses on love as that which exists beyond possessions. The central premise of this work is to argue for a notion of love that is linked to trauma and certainty. It explores the narrative of love as gaze within the narrative of Orpheus and Eurydice as a foundation for reading Biblical and Quranic scripture.
Keywords: Alain Badiou; christianity; Islam; Jacques Lacan; Lacanian psychoanalysis; Psychoanalysis; Slavoj Zizek